2012
DOI: 10.1002/sec.517
|View full text |Cite
|
Sign up to set email alerts
|

Two‐factor mutual authentication with key agreement in wireless sensor networks

Abstract: Wireless sensor networks (WSNs) are getting popular for their deployment in unattended environments, where a registered user can log in to the network and access data collected from the desired sensor. Because of limited resources and computation power in sensor nodes, an authentication protocol should be simple and efficient. M.L. Das proposed a two-factor authentication scheme for WSNs. Because his scheme uses only one-way hash function and XOR operation, it is well suited for resourceconstrained environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 17 publications
0
77
0
1
Order By: Relevance
“…However, the issue of securing and authenticating communication is problematic, because the nodes are vulnerable to attacks and do not have enough capacity for the secure storage of keys [4,5,6]. To solve these security issues, authentication and key agreement schemes using two-factor security, passwords and smart cards have attracted attention and have been studied widely in an effort to guarantee secure communication [7,8,9,10,11,12,13,14]. Unfortunately, many of them still suffer from various attacks and do not provide secure communication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the issue of securing and authenticating communication is problematic, because the nodes are vulnerable to attacks and do not have enough capacity for the secure storage of keys [4,5,6]. To solve these security issues, authentication and key agreement schemes using two-factor security, passwords and smart cards have attracted attention and have been studied widely in an effort to guarantee secure communication [7,8,9,10,11,12,13,14]. Unfortunately, many of them still suffer from various attacks and do not provide secure communication.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, each proposed their own authentication scheme to provide secure user authentication in WSNs. In 2012, Vaidya et al [12] demonstrated that Das’s scheme [8], Khan and Alghathbar’s scheme [10] and Chen and Shih’s scheme [11] had security problems and that none of them provided key agreement. Vaidya et al proposed a two-factor mutual user authentication scheme with key agreement for WSNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubin logic defines actions for dealing with the knowledge in a protocol [36]. The action lists that precede and follow message operations in a principal's behavior list determine a sequence of events performed by the principal during a protocol run.…”
Section: Security Analysis and Verificationmentioning
confidence: 99%
“…A two-factor user authentication protocol [5] which provided strong authentication and a session of key establishment for WSNs existed in 2009, this authentication means that more than one factor is required to authenticate the communicating party in the authentication mechanism. B. Vaidya et al [6] improved the two factor authentication 2nd International Conference on Advances in Mechanical Engineering and Industrial Informatics (AMEII 2016) scheme, because it is vulnerable to stolen smart card attacks and it did not provide a key agreement. J. Kim et al [7] presented that gateway node bypassing attacks and user impersonation attacks are possible using secret data stored in a sensor or an attacker's own smart card in Vaidya et al's scheme.…”
Section: Related Work About Authenticationmentioning
confidence: 99%